(untitled) (Journal of Invasive and Clinical Cardiology, 2024)
Introduction: Cardiovascular diseases (CVDs) are a leading cause of death in the world. In 2015, an estimated 442.7 million prevalent cases of CVD were present worldwide. Cardiovascular diseases account for more than 17 million deaths globally each year. Previous studies identified diabetes mellitus, hypertension, hypercholesterolemia, smoking, alcohol consumption, obesity and sedentary lifestyle as risk factors. Aim of the study: The aim of this study was to determine the risk factors for acute myocardial infarction associated with heart blockage among non-diabetic patients. Methods: This was an observational study conducted in the Department of Cardiology of Jashore Medical College Sadar Hospital, Jashore, Bangladesh during the period from April, 2021 to March, 2022. In this study, we included 120 non-diabetic patients who were diagnosed with myocardial infarction. Result: Mean age was 53.03±11.3 years & most of our patients were male. Among all patients, majority (65%) patients had >60% blockage, followed by 30(25%) patients had 40%-60% artery blockage, and <40% blockage was found in 10% patients. Hypertension, dyslipidemia & dyslipidemia with hypertension, age ≥60 years, family history of CHD, smoking, diabetes & obesity were individual risk factors of CHD among non-diabetic patients. The most common risk factors for heart blockage were age >45 years, high blood pressure, high LDL, unhealthy diet, and stressful life. Conclusion: In our study, we found hypertension, history of CHD, dyslipidemia, dyslipidemia with hypertension, stress, age ≥60 years, and obesity were individual risk factors for CHD. These elements work as crucial risk factors for myocardial infarction in non-diabetic patients. Risk factors like age >45 years, high blood pressure, high LDL, unhealthy diet, and stressful life were responsible for the highest heart blockage in myocardial infarction patients. J Inv Clin Cardiol 2023; 5(2): 38-44